2006
DOI: 10.1007/s00056-006-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Shear-Peel Bond Strength of Orthodontic Brackets on Enamel after Using Pro Seal™

Abstract: Although the statistical evaluation showed no significant negative influence on the shear-peel bond strength either when Pro Seal was used in addition, or when that fluoride-releasing, light-curing sealant was substituted for the bonding agent recommended by the manufacturer, the Weibull analysis showed that the use of Pro Seal in combination with SEP resulted in bond strength values that were less reliably reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…This is in agreement with recently published studies were iBond [31,34] or Ideal1 [20,32,35,36] were investigated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with recently published studies were iBond [31,34] or Ideal1 [20,32,35,36] were investigated.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, Clearfil SE Bond and Transbond Plus achieved similar high bond strength to that of the etch and prime method. These results have also been found in other studies [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…In the unbleached groups, the majority of the bond failure in both groups left more than 90% of the adhesive on the enamel surfaces. This finding is in agreement with Paschos et al 22 In the bleached groups, the mode of bond failure was adhesive/cohesive in nature. Indeed, this mostly mixed adhesive/cohesive failure mode was also found in other studies that stored their samples 2 weeks after bleaching, prior to bonding.…”
Section: Discussionsupporting
confidence: 93%
“…16,12 Bishara et al 16 showed in their in vitro study that Pro Seal sealant did not reduce immediate shear bond strength when compared to Transbond XT primer. Similarly, Paschos et al 22 found no statistically significant difference between Pro Seal sealant and Transbond XT primer when used with adhesive precoated brackets.…”
Section: Discussionmentioning
confidence: 92%
“…Microscopy reveals that only 55.6 µm of enamel are lost in the process. The trend is toward self-etching products, which simplify the procedure in clinicians' hands by combining several bonding steps [26,27]. Self-etching primers are desirable, not least because more enamel is preserved.…”
Section: Bearbeiten Der Gesamten Labialflächementioning
confidence: 99%